The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10384-012-0216-6
|View full text |Cite
|
Sign up to set email alerts
|

Bevel toric multicurve rigid gas-permeable lens for keratoconus

Abstract: Fitting of Twinbel bevel toric improved visual acuity in eyes affected by keratoconus, thus providing a viable alternative for management of such eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…In previous studies on multi-curve HCLs, the HCLs were not designed to have a flat peripheral zone curve; however, the BCVA, duration of HCL wear, and HCL wearing success rates were better than those obtained in this study [17][18][19]. The reason for the poor result of multicurve HCLs in our study may be that most multi-curve HCLs were used for stage 4 cases.…”
Section: Plos Onecontrasting
confidence: 64%
See 1 more Smart Citation
“…In previous studies on multi-curve HCLs, the HCLs were not designed to have a flat peripheral zone curve; however, the BCVA, duration of HCL wear, and HCL wearing success rates were better than those obtained in this study [17][18][19]. The reason for the poor result of multicurve HCLs in our study may be that most multi-curve HCLs were used for stage 4 cases.…”
Section: Plos Onecontrasting
confidence: 64%
“…Higher-order aberrations and contrast sensitivity function were evaluated during HCL wear in some previous studies. Yanai et al [ 18 ] reported no significant difference in higher-order aberrations before and during HCL use. In contrast, Negishi et al [ 20 ] reported that ocular higher-order aberrations increased during HCL wear for keratoconus even when corrected visual acuity was good.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that have evaluated rigid lens correction with corneal lenses in keratoconus have analysed retrospective data in well‐defined clinical populations. These reports provide useful information regarding the range of corneal lens designs that have been utilised in clinical practice; however, objective comparisons are limited by the absence of a control group and/or clearly defined criteria regarding the definition of a successful rigid lens fit. As such, there is currently a lack of high‐quality, controlled prospective clinical trial evidence to provide guidance with regard to the relative merit of different proprietary lens designs.…”
Section: Contact Lens Modalities For Keratoconusmentioning
confidence: 99%
“…Despite the various lens designs of corneal GPs such as spherical, aspheric, multicurve, peripheral toric, 11 and reverse geometry design 12 that are commercially available, the most used for keratoconus is probably the multicurve lenses. The design of the multicurve lens mimics the shape of the cornea in eyes with keratoconus and is designed so that the curvature in the center of the lens is steep, but the curvature becomes flatter toward the periphery.…”
Section: Major Fitting Strategy Of Rigid Gas-permeable Lens Prescriptionmentioning
confidence: 99%